Analisis Indikator Kinerja Zakat Community Development Dalam Rangka Pemberdayaan Mustahik Produktif - Azizah Mursyidah (Islamic Economics Journal, 2019)
This paper is a theoretical article that One of the zakah utilization problems is the short term need of mustahik. Zakah Community Development is one the productive program in BAZNAS aims to empower the poor in aspect education, health, economic and religion aspect. The problem of community program is how to measure the result of the performance of the program as well as outcome and also the impact of the implementation of the program. This study aims to measure the performance indicators of zakah community development to empower mustahiq’s in Indonesia, using ANP (Analytic Network Process). ANP is a qualitative and quantitative research methodology to empasize data collection on the view experts and practitioners, ANP is an easier methodology applied to qualitative study that diverse as decision making, forecasting, evaluation, mapping strategies, resource allocation, and others. Based on the result of zakah performance indicator of community development there are five indicators: (1) Institutional Indicator, (2) Strengthening community capacity Indicator, (3) Development community businesses Indicator, (4) Development of work Indicator, (5) assessment religion Indicator.The most important of ZCD’s Performance Indicators is the partnership development with 9.1% and 48.4 percent of the coefficients Kendalls of expert and practitioner. Meanwhile, improving ZCD’s performance indicator to empower mustahik in Indonesia is a must, this result can be able to be used as the consideration to increase the partnership value. The strategies to ZCD Performance Indicator are:(1) Cooperation multi-stakeholders zakah community development and programs, (2) innovation of ZCD’s program, (3) efficiency ZCD phases of the program.